Learning to change our world? / Per Wickenberg, Harriet Axelsson, Lena Fritzén, Gustav Helldén , Johan Öhman (eds), - Wickenberg, Per [et.al] (2008)
Educational framework in esd, care nature - an ethical dimension in education for sustainable development, moral perspective in selective traditions of enviromental education, formaton of environmental knowledge, abount impact and importance of school gardening in primary schools, enviromental problems - root or fruit of poverty? prospects and preconditions in tanzania, norm supporting structures in environmental education and education for sustainable development; Teachers abs student teachrs on esd, dare to learn for a ssutainable future-a study of teachers as learnen, sustainable development in terms of democracy-an educational challenge for teacher education, experiments for understanding the freenhouse effect, gatokeepers to ecological understanding, natural science for decision-kaking, why abount what teachers´content selection in EE (presentation), student techer´s understanding and concept formation of sustainable development; students´lerning about, in & for ESD, students´reflections over their understanding of ecological processes, learning about environmental issues, post-and undergraduate students´interpretacions of environmental content in education, students{ dialogues and contributions in educations in education for sustainable development, national evaluaion on the theme ´state of the world', the problem of evaluating complex skills on a national basis, life cycles - for caring and leraning about oraganisms and their environment - a starting point towards an understanding of sustainable development, ral life questins and educating for sustainable develo´,emt, ecosystms understanding, models for learning and teaching in environmental sustainability in school.